On fundamental group of Riemannian manifolds with ommited fractal subsets - Mirzaie, R. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We show that if $K$ is a closed and bounded subset of a Riemannian manifold $M$ of dimension $m > 3$, and the fractal dimension of $K$ is less than $m - 3$, then the fundamental groups of $M$ and $M - K$ are isomorphic.